PENGARUH RASIO KEUANGAN TERHADAP PEMBIAYAAN MURABAHAH DI BANK PEMBIAYAAN RAKYAT SYARIAH ADECO LANGSA TAHUN 2013-2016 - Siagian, Yupin Kirana; Budiman, Iskandar; Kismawadi, Early Ridho (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
The independent variables in this study are deposits and financial ratios ofsharia banks which consist of NPF and FDR ratios. This study aims todetermine and analyze the effect of DPK, NPF and FDR on Murabahahfinancing in the SRB. This study used secondary data, which is the form ofpublished Financial Statements of banks obtained from the website of BankIndonesia. The bank's financial report used is quarterly financial report atAdeco Langsa Syariah Adequacy Bank. The data were then analysed by usingthe classical assumption method using multiple linear regression analysis,determination coefficient, F test or simultaneous test and t test or partial test.Hypothesis in this research is DPK, and financial ratio of NPF and ROE bankpartially has significant effect to Murabahah financing, while simultaneouslyfrom the three variables have a significant effect on the provision of financing.The method used in this study is multiple regressions. The results of this studyindicated that DPK and FDR variables have no significant effect on murabahahfinancing, while NPF affects.